2020
DOI: 10.9734/ajarr/2020/v13i230304
|View full text |Cite
|
Sign up to set email alerts
|

Parental Involvement in the Education Development of Indigenous People in Selected Elementary Schools in the Northern Part of Mindanao, Philippines

Abstract: Parents play a vital role in increasing the performance and ensuring the good manners of their children in school. In the context of Indigenous People (IP), parental participation in educating their children is a meaningful involvement that benefits student learning directly. This study aims to determine the parental involvement of indigenous people in selected elementary schools in Northern Part of Mindanao, Philippines. The study specifically identified the profile of the IP parents, parents’ contributory fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
0
0
Order By: Relevance
“…Looking at the situation in the Philippines, during the school improvement plan, it was found that the Orang Asli Primary School faced the issue of implementing programmes and projects that affected the school's performance rating in the target year of their implementation. The fundamental problems that contribute to the issue are the inconsistency of concepts, ambiguity, and confusion about parental involvement (Odinah and Renante, 2020). Whereas, according to Kaomea (2012), many Pacific educators in Hawaii argued that working pacifist indigenous parents did not carry their share of the burden.…”
Section: Problem Statementmentioning
confidence: 99%
“…Looking at the situation in the Philippines, during the school improvement plan, it was found that the Orang Asli Primary School faced the issue of implementing programmes and projects that affected the school's performance rating in the target year of their implementation. The fundamental problems that contribute to the issue are the inconsistency of concepts, ambiguity, and confusion about parental involvement (Odinah and Renante, 2020). Whereas, according to Kaomea (2012), many Pacific educators in Hawaii argued that working pacifist indigenous parents did not carry their share of the burden.…”
Section: Problem Statementmentioning
confidence: 99%
“…(Ignacio,2017). Rapid urbanization and consumption patterns have resulted in a remarkable increase in the volume and diversity of waste, which has become a severe environmental risk (Enteria, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, some factors may hinder parents from actively engaging in their children's school life. Schools have created several initiatives to address this problem and increase parent participation in academic settings [1][2][3]. Some of these initiatives have flourished to yield better outcomes, yet others are not privileged to achieve the same results.…”
Section: Introductionmentioning
confidence: 99%